O narzędziach i wynikach badań = About the tools and the results of the research - Mrozkowiak, M.; Bereznyakova, A. I.; Cheremisina, V. F.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Mrozkowiak M., Bereznyakova A. I., Cheremisina V. F., Zukow W. O narzędziach i wynikach badań = About the tools and the results of the research. Journal of Education, Health and Sport. 2015;5(11):245-260. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33965 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A245-260 https://pbn.nauka.gov.pl/works/670087 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. O narzędziach i wynikach badań About the tools and the results of the research M. Mrozkowiak1, А. И. Березнякова2, В. Ф. Черемисина2, W. Zukow1 M. Mrozkowiak1, A. I. Bereznyakova2, V. F. Cheremisina2, W. Zukow1 1Uniwersytet Kazimierza Wielkiego, Bydgoszcz 1Kazimierz Wielki University, Bydgoszcz 2Национальный фармацевтический университет, г. Харьков 2National University of Pharmacy, Kharkiv Słowa kluczowe: postawa ciała, cechy krwi, narzędzia badawcze, wyniki badań. Keywords: posture, blood, research tools, the results of the research. Streszczenie Pomimo wielu opracowanych koncepcji oceny postawy ciała, prześwietlenie promieniami Roentgena jest nadal metodą najbardziej popularną. Ortopedzi, porównując różne metody leczenia, mają tendencję do formułowania wniosków tylko na podstawie zdjęcia rtg. Należy zauważyć, że badanie z wykorzystaniem mory projekcyjnej nie zastępuje diagnostyki postawy rtg. Bowiem oparta jest na innej zasadzie działania, wykorzystuje między innymi analizę układu kostnego, a zalecana pozycja podczas zdjęcia nie rejestruje postawy habitualnej. Problemy podobnej natury występują także w pomiarze wielkości cech krwi. Dla zachowania wysokiej standaryzacji pobrań i analizy materiału należy zadbać aby: pobór krwi nastąpił przez tą samą osobę i w tych samych warunkach socjalnych, z tego samego odcinka żyły, w tym samym ustawieniem kończyny górnej o rozluźniony mięśniach, strzykawką tej samej firmy, zastosowano te same warunki i metodę analizy krwi. Nie bez znaczenia jest także czas po jakim nastąpiła analiza cech krwi, stosowana procedura analizy i producent stosowanych odczynników. W związku z tym, w ocenie wielkości cech krwi należy brać pod uwagę podawane przez laboratorium analityczne obowiązujące wielkości referencyjne. Abstract Despite the many developed the concept of evaluation of the body posture, overexposure x-ray is still the most popular method. Orthopedists, comparing the various methods of treatment, they tend to formulate proposals on the basis of x-ray pictures. It should be noted that a study using projection moire does not replace diagnostic x-ray attitude. Because it is based on a different principle, inter alia, an analysis of the skeletal system, and recommended items during the photos does not record the attitude of habitual. Problems of a similar nature occur also in measuring the size of blood characteristics. To preserve the high standardisation of donations and material analysis, care should be taken to: collection of blood followed by the same person and the same social conditions, with the same section of the vein at the same setting of the upper extremity of relaxed muscles, inject the same company, the same conditions and method of analysis of the blood. Not without significance is also the time that there had been an analysis of the characteristics of the blood analysis procedure used and the manufacturer used reagents. Therefore, in assessing the size of the blood characteristics have to be taken into account given by the analytical laboratory, the existing benchmarks.